Abscopal Effect after Stereotactic Body Radiotherapy with Nivolumab for Lung Metastasis of Head and Neck Cancer: A Case Report - Masashi Endo; Yukiko Fukuda; Kouhei Okada; Kazunari Ogawa; Michiko Nakamura; Satoru Takahashi; Masahiro Kawahara; Keiko Akahane; Yoshiaki Nagai; Hironori Yamaguchi; Hiroshi Nishino; Harushi Mori; et al. (Case Reports in Oncology, 2023)
Introduction: The abscopal effect (AE) is a phenomenon, in which radiotherapy exerts an antitumour effect on distant lesions outside the primary irradiated area. Although immune checkpoint inhibitors have been widely studied for their potential to enhance the AE and improve patient outcomes, findings in cases of head and neck cancers remain limited. Case Presentation: We report the case of a 72-year-old man who experienced lung oligoprogression during nivolumab treatment for metastatic hypopharyngeal cancer. Stereotactic body radiotherapy (SBRT) was administered to one of the lung lesions, after which both irradiated and nonirradiated lesions regressed. Upon an 18-month follow-up period after SBRT, the patient showed no disease progression or toxicity, and continued receiving nivolumab therapy. Conclusion: The intent behind presenting this case report was to contribute to the accumulation of evidence regarding the AE in cases of head and neck cancer.